1997
DOI: 10.1017/s0031182097001042
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal architecture and components involved in the attachment of Trypanosoma congolense epimastigotes

Abstract: Scanning and transmission electron microscopy of Trypanosoma congolense epimastigotes attached to a plastic substratum shows them to elaborate a complex flagellum filament system and plaque with a highly organized structure. Non-ionic detergent extraction of these cells shows that the resulting cytoskeletons remain attached to the plaque. The subpellicular corset of microtubules can be removed by salt or Ca2+ treatment leaving the axoneme, paraflagellar rod, associated filaments and the plaque. Neither of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Furthermore, it is able to restructure the flagellum to attach to surfaces, generating an extensive flagellum-derived adhesive pad, and does so readily in culture. This allowed an analysis of this process, which occurs in most trypanosomatid lineages (13)(14)(15). Judging by the distribution of morphological traits in trypanosomatids, we propose that Paratrypanosoma morphology is close to that of the last common ancestor of trypanosomatids.…”
Section: Significancementioning
confidence: 91%
“…Furthermore, it is able to restructure the flagellum to attach to surfaces, generating an extensive flagellum-derived adhesive pad, and does so readily in culture. This allowed an analysis of this process, which occurs in most trypanosomatid lineages (13)(14)(15). Judging by the distribution of morphological traits in trypanosomatids, we propose that Paratrypanosoma morphology is close to that of the last common ancestor of trypanosomatids.…”
Section: Significancementioning
confidence: 91%
“…At the site of contact, the flagellar membrane is observed to expand and abundant filamentous material is present, contacting electrondense plaques internal to the membrane and lining the region of attachment (Beattie and Gull, 1997;Tetley and Vickerman, 1985;Vickerman, 1985;Vickerman et al, 1988). Although these junctions have been referred to as 'desmosomes' or 'hemidesmosomes', there is also no evidence to indicate that they are biochemically related to the desmosomes and hemidesmosomes found in higher eukaryotes.…”
Section: Axonemal Cross-linking At the Flagella Connectormentioning
confidence: 99%
“…T. brucei epimastigotes probably need live cells for attachment, because in vivo there is intimate contact between outgrowths of the flagellar membrane with cells of the tsetse salivary gland epithelium [19]. EM studies show that attachment of T. congolense epimastigotes is via hemidesmosomes both in vitro and in vivo [20,22,29]. Comparison of shaken and unshaken cultures showed that attachment is not necessary for epimastigote division but is a prerequisite for differentiation into metacyclics [30].…”
Section: Introductionmentioning
confidence: 99%